Przemoc i śmierć w Karmelu (Kronika Bydgoska, 2014)
This text is a contribution to the history of the Bydgoszcz Carmelites. Based on a source, which was previously unknown to Polish historians, the reasons and efforts of friar Wojciech of Bydgoszcz for a papal dispensation for causing the death of his brother were described. The author also engages in a polemic with a researcher from Switzerland, claiming that the events described in Wojciech’s request took place in the Bydgoszcz monastery.